INFLUENCES OF PHILANTROPHIC ACTIVITIES RUMAH BELAJAR CERIA (RBC) TOWARD THE WELFARE OF SOCIETY IN SUNGAI PEDADO - Mardiah, Siti; Saputra, Rambo (Islamic Economics Program, Faculty of Islamic Economics and Business, 2020)
By utilizing waqf land located in Sungai Pedado village, the Rumah Belajar Ceria community conducts various social activities. The initial goal of this community was to help increase of the level of education in this area. Then the activity continues on the aspect of economic empowerment of the community by conducting Mushroom cultivation. This study aims to describe the activities of the RBC community in improving the social welfare of the Sungai Pedado village community. The research methodology uses a mix of used method with descriptive analysis and the data analysis with the CIBEST models to measure the level of effectiveness of activities on community economic empowerment in the Macmur program. The results showed that the existence of the RBC mushroom livestock program could improve people's welfare and reduce the index of material poverty. The household classification is based on the CIBEST Model roomates is categorized as prosperous (quadrant I) as many as 28 Households, material poor (quadrant II) as many as 2 poor, spiritual Households are absent, and reviews those that fall into absolute poor category are none.